Population dynamics and productivity of Echinogammarus marinus (Leach) in the Mondego estuary throughout three decades - Leite, Nuno Januário Figueiredo (2011)
Dissertação de Mestrado em Ecologia, apresentada ao Departamento de Ciências da Vida da Faculdade de Ciências e Tecnologia da Universidade de Coimbra.